Coping with medical training demands: thinking of dropping out, or in it for the long haul. Issue 9 (1st September 2016) - Rogers, Mary E.; Creed, Peter A.; Searle, Judy; Nicholls, Serena L.
Abstract : Medical trainees are at risk of psychological distress due to training workload demands. Dropping out of medicine has hidden and real costs to both the public and the individual. Using quantitative and qualitative methodologies, this study assessed differences in stress and coping strategies between those serious and not serious about dropping out of medicine. A total of 854 medical students and junior doctors completed a web-based survey assessing training stress, problem-solving coping, seeking support coping, avoidance coping, and risky behaviour coping. Those serious about dropping out of medicine were high on training stress, avoidance coping, and risky behaviour coping. Specifically, males were high on risky behaviour coping, and doctors were high on avoidance coping. Reasons for contemplating dropping out of medicine were professional fit, workload, work–life balance, and the medical education training system. Identification of at-risk groups can inform efforts to design and deliver wellness interventions for medical trainees.